Advances and Applications in Deep Eutectic Solvents Technology - Tiecco, Matteo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint reports advances in the topic of Deep Eutectic Solvents regarding their use as green alternatives in different chemical applications. Studies on the extraction/preconcentration processes of pharmacologically relevant molecules, structural spectroscopic studies, and application in gas purification studies are reported. Two relevant reviews are also published in the context of carbon dioxide conversion and their use in the chemistry of transformations. This reprint therefore aims to summarize some of the pertinent issues in DES chemistry through relevant literature references.